2019
DOI: 10.1016/j.immuni.2018.12.022
|View full text |Cite
|
Sign up to set email alerts
|

The Lupus Susceptibility Locus Sgp3 Encodes the Suppressor of Endogenous Retrovirus Expression SNERV

Abstract: Graphical Abstract Highlights d We identify the suppressor of non-ecotropic (NE) endogenous retroviruses (Snerv) d SNERV1 and SNERV2 are KRAB-ZFPs that bind to the NEERV LTR and recruit KAP1 d Loss of SNERV1/SNERV2 underlies the lupus autoantigen gp70-associated loci Sgp3 and Gv1 d Elevated ERV in SLE patients' blood cells correlates with KRAB-ZFP dysregulation SUMMARY Elevated endogenous retrovirus (ERV) transcription and anti-ERV antibody reactivity are implicated in lupus pathogenesis. Overproduction of non… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 86 publications
1
46
1
Order By: Relevance
“…Interestingly, the same primer sequence is used by various retroviruses, which suggests that a single KRAB-ZFP could potentially restrict a wide range of retroviruses. Recently, a pair of KRAB-ZFPs, known as Suppressor of nonecotropic ERV1 (Snerv1) and Snerv2 were shown via genetic analysis to be required for silencing of nonecotropic ERV (NEERV) expression (Treger et al 2019). In immunodeficient mice, NEERV loci can recombine to generate infectious retroviruses, and expression of NEERV glycoprotein gp70 contributes to lupus nephritis susceptibility Ottina et al 2018).…”
Section: Krab-zfps Also Regulate Host Genes and Viral Activitymentioning
confidence: 99%
“…Interestingly, the same primer sequence is used by various retroviruses, which suggests that a single KRAB-ZFP could potentially restrict a wide range of retroviruses. Recently, a pair of KRAB-ZFPs, known as Suppressor of nonecotropic ERV1 (Snerv1) and Snerv2 were shown via genetic analysis to be required for silencing of nonecotropic ERV (NEERV) expression (Treger et al 2019). In immunodeficient mice, NEERV loci can recombine to generate infectious retroviruses, and expression of NEERV glycoprotein gp70 contributes to lupus nephritis susceptibility Ottina et al 2018).…”
Section: Krab-zfps Also Regulate Host Genes and Viral Activitymentioning
confidence: 99%
“…Notably, there was a large variation in the number of new insertions in these mice, possibly caused by hyperactive polymorphic ETn insertions that varied from individual to individual, epigenetic variation at ETn insertions between individuals and/or the general stochastic nature of ETn mobilization. Furthermore, recent reports have suggested that KRAB-ZFP gene content is distinct in different strains of laboratory mice (37,38), and reduced KRAB-ZFP gene content could contribute to increased activity in individual mice. Although we have yet to find obvious phenotypes in the mice carrying new insertions, novel ETn germ line insertions have been shown to cause phenotypes from short tails (39)(40)(41) to limb malformation (3) and severe morphogenetic defects including polypodia (42) depending upon their insertion site.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, inspection of the chromosomal territory covered by the QTL revealed no known regulator of imprinting. However, the QTL overlaps with a conserved cluster of more than twenty KRAB zinc-finger proteins some of which implicated in sex-specific gene expression (Krebs et al, 2005) and at least two genomic intervals that have previously been linked to disease and developmental phenotypes (Kano et al, 2007;Treger et al, 2019;Wang et al, 2002) (Fig. S4).…”
Section: Qtl Analysis Reveals a Causal Region On Chromosome 13mentioning
confidence: 99%